Magnetic Resonance–Guided High-Intensity Focused Ultrasound (MRgHIFU) Treatment of Symptomatic Uterine Fibroids: An Evidence-Based Analysis - Pron, G (Ont Health Technol Assess Ser, 2015)
BACKGROUND: Magnetic resonance–guided high-intensity focused ultrasound (MRgHIFU) is a noninvasive uterine-preserving treatment alternative to hysterectomy for women with symptomatic uterine leiomyomas (fibroids). Uterine fibroids commonly occur, have a broad impact on women's health and lifestyle, continue to be the main indication for hysterectomy, and represent a costly public health burden. OBJECTIVES: The objectives of the analysis were to evaluate patients’ eligibility for MRgHIFU treatment of symptomatic uterine fibroids and the technical success, safety, effectiveness, and durability of this treatment. The review also compared the safety and effectiveness of MRgHIFU with other minimally invasive uterine-preserving treatments and surgeries for uterine fibroids. METHODS: A literature search was performed on March 27, 2014, using Ovid MEDLINE, Ovid MEDLINE In-Process and Other Non-Indexed Citations, Ovid EMBASE, EBSCO Cumulative Index to Nursing & Allied Health Literature (CINAHL), and EBM Reviews, for studies published from January 1, 2000, to March 27, 2014. RESULTS: The evidence review identified 2 systematic reviews, 2 RCTs, 45 cohort study reports, and 19 case reports involving HIFU treatment of symptomatic uterine fibroids. Eligibility for MRgHIFU treatment was variable, ranging from 14% to 74%. In clinical cohort studies involving 1,594 patients, 26 major complications (1.6%) were reported. MRgHIFU resulted in statistically and clinically significant reductions in fibroid-related symptoms in studies conducted in 10 countries, although few involved follow-up longer than 1 year. Retreatment rates following MRgHIFU were higher in early clinical studies involving regulated restrictions in the extent of fibroid ablation than in later reports involving near-complete ablation. Emergent interventions, however, were rare. Although a desire for fertility was an exclusion criteria for treatment, spontaneous term pregnancies did occur following HIFU. There were no randomized trials comparing MRgHIFU and other guidance methods, other minimally invasive treatments, or surgeries for symptomatic uterine fibroids. Limitations with MRgHIFU included restricted eligibility, requirement for a dedicated MR device to guide the treatment, lengthy procedure time, and loss of MR opportunity time. CONCLUSIONS: For women failing medical therapy and seeking alternatives to hysterectomy for symptomatic uterine fibroids, MRgHIFU provides a safe and effective, noninvasive, uterine-preserving treatment from which they rapidly recover. The treatment advantages of MRgHIFU are potentially offset by restrictive eligibility, lengthy procedure time, and dependence on availability of an MR device. The lack of comparative evidence between MRgHIFU and other, more established uterine-preserving treatments limits informed decision making among treatment options.